2016
DOI: 10.5194/npg-23-205-2016
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal behaviour of the soil water content of a vineyard in northwest Spain during two growing seasons

Abstract: Abstract. Soil processes are characterized by a great degree of heterogeneity, which may be assessed by scaling properties. The aims of the current study were to describe the dynamics of soil water content at three depths in a vineyard under rain-fed and irrigation conditions and to assess the multifractality of these time data series. Frequency domain reflectometry (FDR) sensors were used for automatically monitoring soil water content in a vineyard located in Leiro (Ourense, northwest Spain). Data were regis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Whether soil moisture exhibits a long-range correlation or antipersistence, corresponding time window sizes are defined as corresponding time scales. Fractal or multifractal behaviors have often been studied to describe soil moisture dynamics (Gao et al, 2015;Guerrini & Swartzendruber, 1997;Mirás-Avalos et al, 2016). Various studies (e.g., R. Song et al, 2011;Gao et al, 2015;Ji et al, 2016;Mirás-Avalos et al, 2016) have focused on the features (e.g., fractal dimensions and long-range correlations) of soil moisture dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether soil moisture exhibits a long-range correlation or antipersistence, corresponding time window sizes are defined as corresponding time scales. Fractal or multifractal behaviors have often been studied to describe soil moisture dynamics (Gao et al, 2015;Guerrini & Swartzendruber, 1997;Mirás-Avalos et al, 2016). Various studies (e.g., R. Song et al, 2011;Gao et al, 2015;Ji et al, 2016;Mirás-Avalos et al, 2016) have focused on the features (e.g., fractal dimensions and long-range correlations) of soil moisture dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal or multifractal behaviors have often been studied to describe soil moisture dynamics (Gao et al, 2015;Guerrini & Swartzendruber, 1997;Mirás-Avalos et al, 2016). Various studies (e.g., R. Song et al, 2011;Gao et al, 2015;Ji et al, 2016;Mirás-Avalos et al, 2016) have focused on the features (e.g., fractal dimensions and long-range correlations) of soil moisture dynamics. Various studies demonstrate that soil moisture dynamics present significant long-range correlations in different areas (Gao et al, 2015;R.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors found that multifractal analysis of SWC time series allowed discrimination among SWC patterns in a vineyard with two treatments, irrigated and rainfed (Mirás‐Avalos, Trigo‐Córdoba, da Silva‐Dias, Varela‐Vila, & García‐Tomillo, 2016). In our conditions, the effect of treatment should be related to the fact that both cover crops caused greater soil water evapotranspiration in the vineyard.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, many other systems also demonstrate a multifractal characteristic. Mirás-Avalos et al [7] characterized this lack of homogeneity in soil moisture storage as a complex function of multiple nested processes "related to topographical, geological, edaphic, and vegetation factors." As soil moisture distribution is linked strongly to these independent variables, it can be hypothesized that these attributes can also represent the self-affine fractal qualities of moisture distribution in their own spatial organization.…”
Section: The Self-affine Fractal Property Of Soil Moisturementioning
confidence: 99%